Analisis Framing Tentang Polisi Pada Pemberitaan Tragedi Kasus Kanjuruhan Di Cnnindonesia.Com Dan Detik.Com - Ramadhana, Bayu Pramudya Ahmad; Malau, Ruth Mei Ulina (eProceedings of Management, 2023)
The Kanjuruhan Tragedy is a heart-wrenching event for football enthusiasts, resulting in the loss of 130 lives. The series of riots in Kanjuruhan were closely intertwined with the involvement of the Police, who were on duty to secure the match. This study adopts a constructivist paradigm with the aim of understanding how the event is perceived as a constructed product by the media outlets cnnindonesia.com and detik.com in their coverage of the Kanjuruhan Tragedy, employing data collection techniques such as observation and literature review. The research methodology used is qualitative, employing the framing analysis method of Robert N. Entman, which focuses on two main aspects: issue selection and salience. Additionally, the study aims to explore the construction of reality. The findings of this research indicate that cnnindonesia.com frames the news by prominently highlighting the Police as the main cause of the Kanjuruhan Tragedy. On the other hand, detik.com frames the news by prominently emphasizing the Police's defense against alleged causes of the Kanjuruhan Tragedy and portraying supporters as the instigators of the riots.Keywords-Kanjuruhan Tragedy, Police, Robert N. Entman's Framing Analysis, cnnindonesia.com and detik.com media